Biological Applications of Protein Splicing - Vila-Perelló, Miquel; Muir, Tom W. (Cell, 2010)
Protein splicing is a naturally occurring process in which a protein editor, called an intein, performs a molecular disappearing act by cutting itself out of a host protein in a traceless manner. In the two decades since its discovery, protein splicing has been harnessed for the development of several protein-engineering methods. Collectively, these technologies help bridge the fields of chemistry and biology, allowing hitherto impossible manipulations of protein covalent structure. These tools and their application are the subject of this Primer.